2012
DOI: 10.1364/oe.20.011357
|View full text |Cite
|
Sign up to set email alerts
|

Design of plasmonic grating structures towards optimum signal discrimination for biosensing applications

Abstract: Sensors based on surface plasmon resonances (SPRs) have proven themselves as promising devices for molecular investigations -still there is potential to determine the geometrical parameter set for optimal sensing performance. Here we propose a comprehensive design rule for one-dimensional plasmonic grating structures. We present an analytical approach, which allows for estimation of the grating parameters for best SPR coupling efficiency for any geometry and design wavelength. On the example of sinusoidal grat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…This paper will explore in detail the nature of the plasmonic excitations, their ability to generate large concentrations of optical energy, and the transition from the discrete excitation spectrum of a non-singular surface to the continuous spectrum of a singular metasurface. Sub-wavelength metal gratings couple external light into surface plasmons, efficiently localizing the electromagnetic energy and finding applications in optical bio-sensing and photovoltaics [4][5][6][7][8]. These can be used to control external radiation using metasurfaces [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This paper will explore in detail the nature of the plasmonic excitations, their ability to generate large concentrations of optical energy, and the transition from the discrete excitation spectrum of a non-singular surface to the continuous spectrum of a singular metasurface. Sub-wavelength metal gratings couple external light into surface plasmons, efficiently localizing the electromagnetic energy and finding applications in optical bio-sensing and photovoltaics [4][5][6][7][8]. These can be used to control external radiation using metasurfaces [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The same properties are of interest in biosensing applications, where the strong-field confinement and enhancement aid detection of changes in the refractive index of the grating's environment. Several experimental and theoretical studies, which try to optimize the gratings' design to enhance sensing, exist [3][4][5]. Here, we propose a different method to study gratings based on transformation optics.…”
Section: Introductionmentioning
confidence: 99%
“…Split aptamer sequences that specifically bind to adenosine and ATP were adopted from studies reported in the literature. 55,56 In the presence of the target analyte, the segment S2-AF647 forms a complex with tethered S1-Biotin, whereas in the absence of the target analyte the segments do not interact. The S2-AF647 binding events triggered by the presence of the target analyte were monitored by probing of the gold sensor surface with resonantly excited surface plasmons -PSPs.…”
Section: Resultsmentioning
confidence: 99%
“…SPPs can also be excited through grating coupling of a light beam. Here, a metal surface with corrugations with the appropriate periodicity and depth that allows phase matching is exploited [56]. Since this architecture was not applied in this thesis, it will not be further detailed.…”
Section: Eqmentioning
confidence: 99%
See 1 more Smart Citation